A study of Raphanus sativus and its endophytes as carbonyl group bioreducing agents. (April 2015) - Rodriguez, Paula; Magallanes-Noguera, Cynthia; Menéndez, Pilar; Orden, Alejandro A.; Gonzalez, David; Kurina-Sanz, Marcela; Rodríguez, Sonia
Abstract The reported anti-Prelog selectivity in Raphanus sativus hairy roots prompted us to search for similar activity in other R. sativus systems, such as in vitro germinated sprouts, edible roots, and its associated endophytic microorganisms. Two test substrates were used in these studies: acetophenone and rac-ethyl 2-ethyl-3-oxobutanoate. Endophytes were isolated under substrate selective pressure and individual strains were evaluated for their ability to reduce both substrates. Among the isolates, two bacteria and a fungus having the potential to be used as biocatalysts were found: Bacillus megaterium which reduces acetophenone with excellent anti-Prelog selectivity, and Pseudomonas sp. and Penicillium chrysogenum with enantioselectivity and stereoselectivity for the reduction of rac-ethyl 2-ethyl-3-oxobutanoate, respectively.